Role of trap-induced scales in non-equilibrium dynamics of strongly interacting trapped bosons. (8th June 2016) - Dutta, Anirban; Sensarma, Rajdeep; Sengupta, K
Abstract: We use a time-dependent hopping expansion technique to study the non-equilibrium dynamics of strongly interacting bosons in an optical lattice in the presence of a harmonic trap characterized by a force constant K . We show that after a sudden quench of the hopping amplitude J across the superfluid (SF)-Mott insulator (MI) transition, the SF order parameter | Δ r ( t ) | and the local density fluctuation δ n r ( t ) exhibit sudden decoherence beyond a trap-induced time scale T 0 ∼ K − 1 / 2 . We also show that after a slow linear ramp down of J, | Δ r | and the boson defect density P r display a novel non-monotonic spatial profile. Both these phenomena can be explained as consequences of trap-induced time and length scales affecting the dynamics and can be tested by concrete experiments.